ANALISIS PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA - Ronny Hardiansyah Wicaksana, Alwi Suddin & Marjam Desma Rahadhini (Universitas Slamet Riyadi, 2017)
The purpose of this study is to: 1) Analyze the effect of work environment onemployee performance. 2) Analyze the effect of work motivation on employeeperformance. 3) Analyze the effect of compensation on employee performance and 4)Analyze the independent variables that dominant effect on employee performance. Thistype of research is a survey on employees CV Panca Putra in Karanganyar. This type ofdata uses qualitative data and quantitative data. Data sources use primary data sourcesand secondary data. The population of the research is the employee of CV productiondepartment. Panca Putra in Karanganyar totaling 534 employees. The sample is 80employees with proportional cluster random sampling technique. Data collectiontechniques used questionnaire and literature study. Data analysis techniques usedmultiple linear regression. The results showed that the work environment has asignificant effect on employee performance. Motivation has a significant effect onemployee performance. Compensation has a significant effect on employee performance.Compensation is dominant variable the effect of employee performance.Keywords: work environment, motivation, compensation, employee performance